ChemInform Abstract: Tuning the AIE Activities and Emission Wavelengths of Tetraphenylethene‐Containing Luminogens. Issue 32 (July 2016) - Zhou, Jian; He, Bairong; Xiang, Jiayun; Chen, Bin; Lin, Gengwei; Luo, Wenwen; Lou, Xiaoding; Chen, Shuming; Zhao, Zujin; Tang, Ben Zhong
Abstract: The structure‐property correlation of the luminogens (I) and (II), optical properties, fluorescence lifetimes, electronic structures, electrochemical properties, and electroluminescence properties are investigated.